Analisis Persepsi Kualitas Terhadap Perilaku Konsumen pada Perusahaan Minyak Kita - Ardhika Dhiyaulhayat; Halimah Zahrah; Muhammad Ilham Fauzul; Muhammad Arif Hidayat (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This analysis aims to examine the impact of shrinkflation practices on consumer perceptions of quality and loyalty to ‘Minyak Kita’ cooking oil products. Shrinkflation is a strategy of reducing product content without adjusting prices, implemented by manufacturers in response to rising production costs. This study employs a qualitative method with a literature review approach from various books and scientific journals. The analysis findings indicate that shrinkflation without clear communication can reduce consumers' perceptions of product quality and trust in the brand. This situation leads to a shift in loyalty from affective loyalty to calculative loyalty, which is more susceptible to brand switching. Additionally, lack of transparency in shrinkflation practices may violate business ethics principles and damage brand image in the long term. Therefore, companies should consider adopting honest communication approaches to maintain sustainable relationships with consumers.